Prevalence of asthma and chronic obstructive pulmonary disease in Aboriginal and non-Aboriginal populations: A systematic review and meta-analysis of epidemiological studies - Ospina, Maria B (Pulsus Group Inc, 2012)
BACKGROUND: Asthma and chronic obstructive pulmonary disease (COPD) have considerable potential for inequities in diagnosis and treatment, thereby affecting vulnerable groups. OBJECTIVE: To evaluate differences in asthma and COPD prevalence between adult Aboriginal and non-Aboriginal populations. METHODS: MEDLINE, EMBASE, specialized databases and the grey literature up to October 2011 were searched to identify epidemiological studies comparing asthma and COPD prevalence between Aboriginal and non-Aboriginal adult populations. Prevalence ORs (PORs) and 95% CIs were calculated in a random-effects meta-analysis. RESULTS: Of 132 studies, eight contained relevant data. Aboriginal populations included Native Americans, Canadian Aboriginals, Australian Aboriginals and New Zealand Maori. Overall, Aboriginals were more likely to report having asthma than non-Aboriginals (POR 1.41 [95% CI 1.23 to 1.60]), particularly among Canadian Aboriginals (POR 1.80 [95% CI 1.68 to 1.93]), Native Americans (POR 1.41 [95% CI 1.13 to 1.76]) and Maori (POR 1.64 [95% CI 1.40 to 1.91]). Australian Aboriginals were less likely to report asthma (POR 0.49 [95% CI 0.28 to 0.86]). Sex differences in asthma prevalence between Aboriginals and their non-Aboriginal counterparts were not identified. One study compared COPD prevalence between Native and non-Native Americans, with similar rates in both groups (POR 1.08 [95% CI 0.81 to 1.44]). CONCLUSIONS: Differences in asthma prevalence between Aboriginal and non-Aboriginal populations exist in a variety of countries. Studies comparing COPD prevalence between Aboriginal and non-Aboriginal populations are scarce. Further investigation is needed to identify and account for factors associated with respiratory health inequalities among Aboriginal peoples.